Sequence stratigraphic evaluation for the Abu Madi Formation, Abu Madi/El Qar'a/Khilala gas fields, onshore Nile Delta, Egypt - Farouk I. Metwalli; Amir Ismail; M.S. Metwally; Ibrahim M. El Shafei (Petroleum Research, 2023)
The present study aims to integrate a large set of geological and geophysical data into a comprehensive model describing the depositional features of the Abu Madi/El Qar'a/Khilala gas fields. The model is based on the sequence stratigraphic framework of the Abu Madi Formation defined using cores, well logs, and time-migrated seismic data. Seismic trace attribute sections and relative acoustic impedance sections are also used. A possible depositional pattern for the main Level III is established, based on the lithological and petrophysical information derived from the seismic data analysis. The Abu Madi Formation can be regarded as a depositional sequence recording the progressive drowning of the incised valley. The sequence is bounded at the base by an erosional unconformity, created by a drop in the level of the Late Messinian Sea, and at the top by a drowning unconformity related to the Early Pliocene transgression. The bottom of Level II divides the Abu Madi sequence into two smaller sequences. In both sequences, gas-bearing traps can be found in the Lowstand Systems Tracts, represented by the fluvial Level III and fluvial-deltaic Level II, respectively.